2015
DOI: 10.1039/c5cy00647c
|View full text |Cite
|
Sign up to set email alerts
|

Highly active tin(iv) phosphate phase transfer catalysts for the production of lactic acid from triose sugars

Abstract: Lactic acid (LA) is an important intermediate in the fine chemical industry because it is utilized as a building block for the production of biodegradable plastics. In this study, a series of tin phosphate phase transfer catalysts modified with several surfactants have been prepared by a facile one-pot synthesis method and tested for the direct conversion of trioses to LA under hydrothermal conditions. Poly(ethylene glycol) (PEG) was identified as the most promising surfactant, and the product distribution clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 59 publications
(135 reference statements)
3
42
0
Order By: Relevance
“…† The total acidity of the catalyst decreased with increasing the calcination temperature, as similarly reported by another study using tin phosphate catalyst. 41 Similar observation (a higher calcination temperature led to a decrease in the intensity of the Brønsted and Lewis acid sites) was obtained from the pyridine FT-IR measurements to be presented in the subsequent section.…”
Section: Nh 3 -Tpdsupporting
confidence: 78%
“…† The total acidity of the catalyst decreased with increasing the calcination temperature, as similarly reported by another study using tin phosphate catalyst. 41 Similar observation (a higher calcination temperature led to a decrease in the intensity of the Brønsted and Lewis acid sites) was obtained from the pyridine FT-IR measurements to be presented in the subsequent section.…”
Section: Nh 3 -Tpdsupporting
confidence: 78%
“…There are only a few studies in the literature that used water as solvent to produce lactic acid, and they focused on the performance of zeolites (Y, USY, ZSM‐5, Beta and Mordenite), substituted zeolites (Zr‐, Ti‐ and Sn‐Beta, and Sn‐MCM‐22), tin phosphates and carbon−silica composites . These authors concluded that the Lewis acid sites can catalyze the formation of lactic acid from trioses and that the catalyst activity was associated with the strength of such sites; the stronger the Lewis acid sites the more active the catalyst …”
Section: Introductionmentioning
confidence: 99%
“…With the rapid growth of the world economy, the high dependence on fossil fuels has caused serious environmental problems and requires groundbreaking improvements in clean technology that will take advantage of renewable energy sources. 1,2 Biomass represents an abundant and renewable carbon resource that can be transformed into liquid fuels and value-added chemicals. The catalytic conversion of biomass has been the subject of intense research efforts in recent years.…”
Section: Introductionmentioning
confidence: 99%